Time, ontology and writing:: notes on history and literature from A paixão segundo G.H. (1964), by Clarice Lispector and O som do rugido da onça (2021), by Micheliny Verunschk (Ágora Journal, 2023)
In this paper we analyze two distinct works from disparate contexts. They are the novels “A Paixão Segundo G.H.” (Clarice Lispector) and “O Som do Rugido da Onça” (Micheliny Verunschk). Since they are different narratives, we seek to reflect on common axes, mobilizing elements around time, ontology, and writing. We are interested in the power of the literary and the fictional in their capacity to destabilize the established time, and this through language and its discursive strategies, issues that present themselves, dissonantly, in both selected texts.
Keywords: history and literature; narrative; time; ontology